Mars trilogy : a princess of Mars, the gods of Mars, the warlord of Mars - Burroughs, Edgar Rice, 1875-1950 (Burroughs, Edgar Rice, 1875-1950. Mars novels, 2012)
Brings together the first three John Carter of Mars books, illustrated by well-known fantasy illustrators, as John arrives on Mars for the first time and works to win the heart of a princess, fights the dreaded Black Pirates, and faces an evil that threatens to destroy the planet and everything he has grown to love.